Analisis Komposisi Ideal Dana Tabarru’-Ujrah Metode Dynamic Financial Analysis Perusahaan Asuransi Jiwa Syariah Di Indonesia - Billy Purwocaroko N; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The aim of this study was to determine the ideal composition of tabarru'-ujrah fund on Sharia Life Insurance company in Indonesia through Dynamic Financial Analysis method. This research is a quantitative with a simulation approach. The simulation model was Monte Carlo simulation. The data using a secondary data from the financial statements of insurance sharia life insurance companies published between 2012-2014. There are two variables that influence the formation of the composition tabarru’ the claims and Retakaful. The results of this study indicate that the ideal composition tabarru'-ujrah funds obtained amounted to 68.73%: 31.27%. The phenomenon that occurs is the composition tabarru’ which showed a reading below 50%, the life insurance industry sharia set much ujrah in every contribution at the time of composition claims and Retakaful in a low position, and ROI DPS received until the end of the forecasting declining and even minus.